MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPS MELALUI PENERAPAN STRATEGI PEMBELAJARAN IDEAL DI KELAS VII SMP TRI BHAKTI PEKANBARU T.A 2018/2019 - May Fanra; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the low learning outcomes of students insocial studies subjects VII grade SMP Tri Bhakti Pekanbaru. Based on these problems,the formulation of the problem in this study is whether the application of IDEALlearning strategies can improve the learning outcomes of grade VII students of SMP TriBhakti Pekanbaru. The purpose of this study was to determine the activities of teachersand students in the implementation of the learning process by using IDEAL strategy andto determine the effect of this learning strategy on the learning outcomes of students ofclass VII SMP Tri Bhakti Pekanbaru on social studies subjects. This research wasconducted in two cycles, in the first cycle the learning outcomes of students reached aclassical completeness of 61.90% and increased in the second cycle to reach 90.47%.Based on the results of these studies it can be concluded that the application of IDEALlearning strategies can improve student learning outcomes in social studies class VIISMP Tri Bhakti Pekanbaru.Key Words: IDEAL Strategy, Learning Outcomes